Model-based needle control in prostate percutaneous procedures. (January 2013) - Maghsoudi, Arash; Jahed, Mehran
In percutaneous applications, needle insertion into soft tissue is considered as a challenging procedure, and hence, it has been the subject of many recent studies. This study considers a model-based dynamics equation to evaluate the needle movement through prostate soft tissue. The proposed model estimates the applied force to the needle using the tissue deformation data and finite element model of the tissue. To address the role of mechanical properties of the soft tissue, an inverse dynamics control method based on sliding mode approach is used to demonstrate system performance in the presence of uncertainties. Furthermore, to deal with inaccurate estimation of mechanical parameters of the soft tissue, an adaptive controller is developed. Moreover, through a sensitivity analysis, it is shown that the uncertainty in the tissue mechanical parameters affects the system performance. Our results indicate that the adaptive controller approach performs slightly better than inverse dynamics method at the expense of fine-tuning the additional gain parameter.